Opportunities of Passive Income in DeFi Sector - Kern, Lukáš (2022)
Currently, the rising inflation and traditional financial instruments offering only small returns caused the attention of many investors to shift towards the crypto space, specifically decentralized finance (DeFi). DeFi offers many opportunities for passive income. However, it compensates for these incomes with an increased amount of risk. This thesis provides a coherent overview of the crypto space, including new trends, promises of DeFi, and associated risks. This diploma thesis aimed to evaluate different possibilities of passive income in the DeFi sector. In order to answer this question, Aave and Compound were assessed as prominent borrowing and lending platforms. The historical data was analyzed, together with a forecast in the ARIMA model for the future outlooks. The findings suggest that in the current bear market conditions, the risks with the evaluated opportunities are too high, therefore, the investor should not proceed with passive income options evaluated in the thesis. One of the solutions might be waiting for the market to turn around and capitalize on new opportunities. Alternatively, the investor can allocate funds into some centralized finance (CeFi) projects, which still offer reasonable returns.